2005
DOI: 10.1111/j.1600-079x.2005.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum melatonin circadian profiles in women suffering from cervical cancer

Abstract: Although there is an increasing evidence that the pineal gland may play a role in human malignancy, the studies on melatonin concentrations in different types of malignant tumors brought about controversial results. However, changes in melatonin concentrations have been observed in some types of human malignant tumors. Therefore, we decided to study the circadian melatonin rhythm in patients suffering from cervical cancer in different stages of progression and to compare them with those in subjects free from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 16 publications
1
43
1
3
Order By: Relevance
“…In our own laboratories, we have previously shown that melatonin administration ameliorates hypertension in the spontaneously hypertensive rat (20). Relevant to this investigation is the fact that the production of melatonin is greatly impaired in CKD in animals and humans (13,50,51).…”
mentioning
confidence: 92%
“…In our own laboratories, we have previously shown that melatonin administration ameliorates hypertension in the spontaneously hypertensive rat (20). Relevant to this investigation is the fact that the production of melatonin is greatly impaired in CKD in animals and humans (13,50,51).…”
mentioning
confidence: 92%
“…Cross-sectional studies have shown lower melatonin levels in women with endometrial cancer (13,14). An MT2 melatonin receptor subtype that may mediate the cancer-protective effect of melatonin has been described in a human endometrial cancer cell line (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have demonstrated the effect of melatonin on the sex hormones of female rats (25,68,69). We hypothesized that the effects of Mel/ Thea on seizures may be different between OVX and treatment-naive female rats.…”
Section: Discussionmentioning
confidence: 99%